Implementasi Housekeeping sebagai Upaya Preventif Kecelakaan Kerja PT XYZ di Kota Balikpapan - Lina Yuliana; Savira Nava (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Housekeeping is one of the risk controls in the control hierarchy which aims to organize a good work environment. Setting up a good work environment has a big impact on preventing wasted work time. Based on data obtained from RIDDOR (The Reporting of Injuries, Diseases and Dangerous Occurrences Regulations) that 35% of the injuries received by workers were due to slips, trips, and falls from a height. Work accidents that have occurred at PT XYZ are minor injuries, scratches by sharp objects and tripping. The type of research in this research is descriptive qualitative research. The research was conducted in the warehouse area. The research subjects were 6 workers who were involved in repair and sales activities. Data collection techniques are observation and interviews. The variables in this study consisted of each housekeeping component as a variable, namely Concise, Neat, Clean, Treat, and Diligent. The implementation of housekeeping in the company's warehouse area is included in the ineffective category, with each value being concise (60%), neat (30%), clean (75%), caring (35%), and diligent (50%). The recommendations given are to improve the principles of neatness, care, and diligence in accordance with the findings at the work location, including making an inventory list of equipment and goods laying plans, ensuring that supporting housekeeping work principles are installed, and providing regular training and education so that workers understand and can implement housekeeping principles properly. Keywords: Accident; Housekeeping; Implementation; Prevention; Work